Peran Kinerja Lingkungan dalam Memoderasi Faktor-Faktor Pengungkapan Emisi Karbon - Wilda Asyrofa; Adelina Citradewi (PUBLIKASI RISETMAHASISWA AKUNTANSI, 2025)
This study aims to determine the role of environmental performance in moderating the influence of institutional ownership, profitability, and firm size on disclosure of carbon emissions. The population in this study is energy sector companies and basic materials listed on the IDX in 2023. Sampling using purposive sampling technique and as many as 67 companies. Data testing and analysis were carried out by multiple linear regression analysis and Moderated Regression Analysis (MRA) with SPSS 25. The results in this study that, institutional ownership and profitability have no positive and significant effect on disclosure of carbon emissions. Firm size affects the disclosure of carbon emissions. Institutional ownership and firm size cannot moderate the relationship between environmental performance and carbon emission disclosure. Profitability can moderate the relationship between environmental performance and disclosure of carbon emissions